Project trash bag creating in innovative solution for trash control in Mt. Apo National Park - Tanoco, Marjorie May U.
Trash bags were everyday objects that were often overlooked as an important tool in delivering messages to a wide variety of audiences. This thesis focused on designing a trash bag as a medium of information for a unified solid waste management system of the KMM eco-Triangle at Mt. Apo Nature Park. There were two main target audience for this design project ? The Local Government Units (LGU)s) and the mountaineers. The designer was able to address the needs of both target audiences in the design by using the messaging pyramid as a guide in determining the design elements.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts